Commemorating conflict : Greek monuments of the Persian Wars - Duffy, Xavier, (Archaeopress Publishing Ltd, 2018)
A holistic study of how the Greek peoples (of primarily the classical period) collectively commemorated the Persian Wars. This work analyses commemorative objects, places, and groups for a complete representation of the commemorative tradition.